2020
DOI: 10.3390/su12156038
|View full text |Cite
|
Sign up to set email alerts
|

Driving Sustainability in Dairy Farming from a TBL Perspective: Insights from a Case Study in the West Region of Santa Catarina, Brazil

Abstract: All companies in agribusiness supply chains need to be aware of the best use of available resources, which demands an integrated assessment of environmental, economic and social aspects, i.e., the Triple Bottom Line (TBL). Such analysis allows us to get a more balanced and complete understanding of the real performance of companies, supply chains and industries. Companies in the upstream of agribusinesses supply chains present some limitations, but can contribute significantly to the overall sustainability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
1
17
0
4
Order By: Relevance
“…This program was one of the first of its kind, but has been slowed down by excessive bureaucracy, excessively high interest rates, political disinterest of the actual government, and low public awareness [29]. Zanin et al [1] highlights that punctual initiatives of quality and sustainability are found at the company level, or in the case of some short duration regional actions. The program "Balde Cheio" (or Full Bucket in English) from EMBRAPA (Brazilian agricultural research company: https://www.embrapa.…”
Section: Sustainable Supply Chain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…This program was one of the first of its kind, but has been slowed down by excessive bureaucracy, excessively high interest rates, political disinterest of the actual government, and low public awareness [29]. Zanin et al [1] highlights that punctual initiatives of quality and sustainability are found at the company level, or in the case of some short duration regional actions. The program "Balde Cheio" (or Full Bucket in English) from EMBRAPA (Brazilian agricultural research company: https://www.embrapa.…”
Section: Sustainable Supply Chain Managementmentioning
confidence: 99%
“…International trade is framed by a set of rules and norms defined by international or bilateral agreements which companies doing business beyond their frontiers must respect. However, in addition to such rules and standards, companies are also urged to adhere to contemporary social values as well as environmental and moral principles and norms, which societies consider to be adequate in different parts of the world [1]. These issues have led to a discussion in recent years about the role of companies in society and the ethical foundations of economic management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para Broccardo & Zicari (2020), a sustentabilidade vive um momento de rompimento de paradigmas, ou seja, passou de um tema discutido apenas no âmbito acadêmico para um tema conhecido como propulsor da criação de valor, sobretudo em pequenos produtores rurais (Zanin, Dal Magro, Kleinibing Bugalho, Morlin, Afonso & Sztando, 2020) e pequenas empresas (De Camargo, Zanin, Mazzioni, De Moura & Afonso, 2018) que procuram aliar práticas de sustentabilidade a um método alternativo de produção, tendo por base a relação de trabalho justa e transparente, além de contribuir para melhoria de condições de vida dos produtores de países em desenvolvimento (Sama, Crespo-Cebada, Díaz-Caro, Escribano & Mesías, 2018). Essa prática produtiva, conhecida como comercio justo informa ao consumidor final que os produtos que estão sendo adquiridos foram obtidos usando sistemas de produção que atingem os objetivos socioambientais (Dragusanu, Giovannucci & Nunn, 2014;Ramos, Afonso & Rodrigues, 2020).…”
Section: Introductionunclassified
“…Já a atividade leiteira, por desenvolver outras atividades pecuárias e agrícolas dentro de um mesmo campo de análise, é considerada uma atividade complexa (Yamaguchi, Oliveira & Martins, 2005). Nesse sentido, Zanin et al (2020) aduzem que geralmente são várias unidades de negócio relacionadas a um grande negócio, sendo que outras atividades são desempenhadas concomitantemente como a criação de animais, produção de leite, alimentação, sanidade e reprodução, além de produzir a alimentação para os mesmos. Spies (2014) assevera que a produção de leite no Brasil é uma das cadeias produtivas do agronegócio que tem os maiores ganhos marginais a incorporar em todos os seus elos de produção nos próximos anos.…”
Section: Introductionunclassified